2016
DOI: 10.1128/aac.02714-15
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin 24-Hour Area under the Curve/Minimum Bactericidal Concentration Ratio as a Novel Predictor of Mortality in Methicillin-Resistant Staphylococcus aureus Bacteremia

Abstract: T he incidence of methicillin-resistant Staphylococcus aureus (MRSA) infections in health care and community settings has increased in recent years (1). Vancomycin (VAN) has been a mainstay in the armamentarium against MRSA for nearly half a century, but changes in susceptibility patterns have presented new treatment challenges (2). The gradual reduction in susceptibility of MRSA isolates to VAN occurring over the last 2 decades has been associated with increased treatment failure and mortality (3, 4). While t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Neither vancomycin trough concentrations nor AUC correlated with treatment failure in this pediatric patient population with a variety of bloodstream infections (Table 4 and Fig. S3), although several studies in adults with methicillin-resistant Staphylococcus aureus bloodstream infections concluded that the PKPD endpoint of an AUC/MIC value of Ն400 mg•h/liter was clinically relevant (16)(17)(18). A plausible explanation for this discrepancy is the large number of coagulase-negative Staphylococcus infections ( Table 3).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Neither vancomycin trough concentrations nor AUC correlated with treatment failure in this pediatric patient population with a variety of bloodstream infections (Table 4 and Fig. S3), although several studies in adults with methicillin-resistant Staphylococcus aureus bloodstream infections concluded that the PKPD endpoint of an AUC/MIC value of Ն400 mg•h/liter was clinically relevant (16)(17)(18). A plausible explanation for this discrepancy is the large number of coagulase-negative Staphylococcus infections ( Table 3).…”
Section: Discussionmentioning
confidence: 91%
“…Coagulase-negative Staphylococcus infections are likely the result of line infections (25) or contamination and cause limited morbidity. For the remaining 22 Gram-positive bloodstream infections, there was insufficient statistical power to refute AUC target attainment of Ն400 mg•h/liter (16)(17)(18). The fact that only 22 of 785 patients had confirmed Gram-positive isolates on blood culture highlights the lack of infections at the study center, possibly due to good infection control procedures, and shows how difficult running prospective pediatric antimicrobial clinical trials is when so few patients have identifiable infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 There is poor correlation between vancomycin trough levels and clinical outcomes in the therapy of S. aureus infections. 14 The AUC/MIC pharmacodynamic index is best predictive of vancomycin efficacy, [15][16][17] and trough e8…”
Section: Discussionmentioning
confidence: 99%